Synthesis and characterization of new complexes of Co+2 , Ni+2 , Cu+2 and Zn+2 with (Sodium acetate thio ) ethylene ligands - Baghdad Science Journal (مجلة بغداد للعلوم, 2013)
This research involves the preparation of new ligands 1,1,2,2- tetrakis (sodium acetate thio)ethylene(L1) and 1,1,2- tris(sodiumacetatethio) ethylene(L2), through the reaction of disodium thioglycolate) with tetra chloro ethylene or tri chloro ethylene in (1:4) or (1:3) moler ratio . Homodinucliar complexes of general formlu [M2(L1)] and [M2(L2)ClH2O] , when M= Co(II), Ni(II), Cu (II) and Zn(II) also mono nuclear complexes of general formula [M(L2)] . The prepared complexes were characterized using spectral method (UV/Visible/ IR) , metal content analysis , magnetic and atomic measurements . The spectral and magnetic measurement indicats that some complexes have tetrahedral or square planar complexes environtment .